Curcumin ameliorates peritoneal fibrosis via inhibition of transforming growth factor-activated kinase 1 (TAK1) pathway in a rat model of peritoneal dialysis - Jun-Li Zhao; Ting Zhang; Xia Shao; Jun-Jun Zhu; Mei-Zi Guo (BMC, 2019)
Abstract Background Peritoneal fibrosis (PF) remains a serious complication of long-term peritoneal dialysis (PD). The goal of this study was to investigate the anti-fibrotic effects of curcumin on the PF response to PD and its' mechanism. Methods Male Sprague-Dawley rats were infused with 20 mL of 4.25% glucose-based standard PD fluid for 8 consecutive weeks to establish PF model and then divided into five groups: Control, received sham operation and 0.9% physiological saline; PD, received 4.25% standard PD fluid; Curcumin, PD rats injected intraperitoeally with curcumin for 8 weeks at doses of 10, 20 or 40 mg/kg. Masson's staining was performed to evaluate the extent of PF. Peritoneal Equilibration Test (PET) was conducted to assess ultrafiltration volume (UFV) and mass transfer of glucose (MTG), quantitative RT-PCR, and immunohistochemistry or western blotting were performed to measure the expression levels of inflammation and fibrosis-associated factors. We also detected the TGF-β1 in peritoneal fluid by ELISA. Results Compared with the control group, the PD rats showed decreased UFV (2.54 ± 0.48 to 9.87 ± 0.78 mL, p < 0.05] and increased MTG (18.99 ± 0.86 to 10.85 ± 0.65 mmol/kg, p < 0.05) as well as obvious fibroproliferative response, with markedly increased peritoneal thickness (178.33 ± 4.42 to 25.26 ± 0.32um, p < 0.05) and higher expression of a-SMA, collagen I and TGF-β1. Treatment with curcumin significantly increased UFV, reduced MTG and peritoneal thickness of PD rats. The elevated TGF-β1 in peritoneal fluid of PD rats was significantly decreased by curcumin. It attenuated the increase in protein and mRNA of TGF-β1, α-SMA and collagen I in peritoneum of PD rats. The mRNA expressions of TAK1, JNK and p38, as well as the protein expressions of p-TAK1, p-JNK and p-p38 in peritoneum of PD rats were reduced by curcumin. Conclusions Present results demonstrate that curcumin showed a protective effect on PD-related PF and suggest an implication of TAK1, p38 and JNK pathway in mediating the benefical effects of curcumin.